Analyzing Sense and Reference in Students’ Descriptive Writing Based on Emojis and Hashtags on Instagram - Nurmahyuni Asrul; Natanael Saragih (English Education Study Program FKIP Universitas Alwashliyah Medan, 2026)
This mini-research explores how 9th-grade students interpret and apply the sense and reference of emojis and hashtags in their descriptive writing on Instagram. With the rise of multimodal communication in the digital age, Instagram's combination of images, text, emojis, and hashtags has transformed how students express themselves. This study investigates how these symbols influence students' ability to construct sense and reference in their descriptive texts. Using qualitative methods, 30 students from SMP Shafiyyatul Amaliyyah in Medan, provided Instagram posts that incorporated emojis and hashtags in descriptive contexts. Semi-structured interviews further explored their interpretations. The data revealed that emojis primarily served to convey emotions or visually enhance descriptions, while hashtags categorized themes or referenced specific topics. A majority of students (73%) used emojis and hashtags effectively to enhance their descriptive writing, while 27% misused or overused these symbols, leading to unclear or inappropriate references. The research applies Gottlob Frege's theory of sense and reference to analyze how students use emojis and hashtags to convey meaning. The study concludes that while students can integrate digital symbols effectively, there are challenges in their contextual application. This research highlights the importance of teaching students how to use multimodal elements meaningfully in academic writing. Keywords: Emojis, Hashtags, Descriptive Writing, Sense and Reference